2023
DOI: 10.3390/biology12050726
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Lowering Effects of Imeglimin and Its Possible Beneficial Effects on Diabetic Complications

Abstract: Mitochondrial dysfunction is a prominent pathological feature of type 2 diabetes, which contributes to β-cell mass reduction and insulin resistance. Imeglimin is a novel oral hypoglycemic agent with a unique mechanism of action targeting mitochondrial bioenergetics. Imeglimin reduces reactive oxygen species production, improves mitochondrial function and integrity, and also improves the structure and function of endoplasmic reticulum (ER), changes which enhance glucose-stimulated insulin secretion and inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…This report highlights a case of a 55-year-old male with T2D, demonstrating a remarkable response to imeglimin (Twymeeg) over a short period [17]. In this case, HbA1c decreased from 10.9% to 6.8% in just 3 months.…”
Section: Discussionmentioning
confidence: 65%
“…This report highlights a case of a 55-year-old male with T2D, demonstrating a remarkable response to imeglimin (Twymeeg) over a short period [17]. In this case, HbA1c decreased from 10.9% to 6.8% in just 3 months.…”
Section: Discussionmentioning
confidence: 65%
“…Improving inflammation and stress markers may occur not only in pancreatic β-cells but also in vascular endothelium. There have been several reports about the possible effects of imeglimin on endothelial dysfunction [ 22 , 23 ]. For example, it was reported that imeglimin treatment improved endothelial function in subjects with type 2 diabetes by enhancing postprandial blood flow-mediated dilation.…”
Section: Introductionmentioning
confidence: 99%
“…Imeglimin Hydrochloride (also called Imeglimin) a recently approved oral anti-diabetic drug is a first of the class of tetrahydratriazone drug called "glimins" [9]. Chemically Imeglimin Hydrochloride is-(R)-6-imino-N,N,4-trimethyl-1,4,5,6-tetrahydro-1,3,5-triazin-2-amine hydrochloride.…”
Section: Introductionmentioning
confidence: 99%